KEMAMPUAN MAHASISWA DALAM MEMBUAT COMPREHENSION QUESTIONS - Pudiyono Pudiyono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
The aims of the research were to find out (a) the level of the students’ ability in making comprehension questions, (b) the students’ map of problems in making comprehension questions. The population of the research was all students joining Reading 4 academic year 2016, totaling to 30 students, while the sample was taken from all students. The result of data analysis showed that the average ability of the students, with score more than 70 reached 66.66%. In details, only 4 of the samples (13.33%)) got no wrong answers or an A. Those who got good achievement (B), considered as majority, amounted to 16 students (53.33%). The participants achieving enough grades (C) reached 7 students or 23.33%. The last level achieved in this research was D with the number reaching 3 (10%). The map of problems laid on their inability in identifying between yes/no and WH questions, inverted sentence, choosing the right auxiliary and verbs and their spelling ability. Keyword: comprehension, questions, inversion, problem map, ability